Biocemical studies of alkaline phosphatase for cancer patients - Abdulrahman K. Loay; Aljebory M. Abdul-hussien (College of Pharmacy / Mustansiriyah University, 2004)
The activity of alkaline phosphates (ALP) was determined by the calorimetric method of kin and Armstrong in serum of 303 cancer patients and 42 normal healthy controls. The ANOVA test of type, age sex and stage of disease ,the results showed that the ALP activity was higher in cancer patients then normal (p=0.000),this incensement could be used as a tumor marker (significant difference p=o.ooo) detected bone & liver cancer and to detect metastases to the organ . The enzyme activity reached its highest level in the stage group (40-50 years). The results also show that there are no significant differences of ALP activity between males and females while the activity was increased with the development of disease stage. Regan isoenzyme (RI) of ALP was elevated in about 10%-20% of cancer patients and was higher in pancreas ,cervix ,ovarian than stomach ,lung and breast .